Peran Perempuan Dalam Pembangunan Desa di Desa Wisata Lontar Sewu Selama Masa Pandemi - Priani, Tribekti Wahyu; Priani, Tribekti Wahyu (Paradigma, 2022)
The role of women is very important in the process of sustainable development. Women have an important role as development subjects who can plan, implement, monitor/control, and enjoy the final results. The role of women as subjects of development can occur from vulnerable national development to rural areas. The village development in Hendrosari Village has developed a tourism village concept, which is named Lontar Sewu Tourism Village. The development carried out from 2019 to 2020 brought new changes and provided benefits to the people of Hendrosari Village, one of which was the women’s community. The existence of the development of the Lontar Sewu Tou rism Village provides many benefits for the community of women who make it possible to join the public sphere by working in the tourist village that has been built. This study uses a qualitative method with the perspective of Women in Development. The results of this study prove that the development of the Lontar Sewu Tourism Village also focuses its development goals on women’s communities, so that they receive many benefits from the village development. In addition, with the opening of the Lontar Sewu Tourism Village, the women’s community is more productive by working there, the women’s community also receives a lot of training so that it increases the creativity and independence of the women’s community, and the involvement of women’s roles in the Tourism Village can increase the family economy and the economy village. Keywords: Role, Women, Village Development, Tourism Villag